Women in Statutory Bodies of State Treasury-Listed Companies and Corporate Financial Performance - Błaszczyk, Alina (INSTED: Interdisciplinary Studies in Education & Society, 2025)
The article presents an analysis of State Treasury-owned companies continuously listed on the main market of the Warsaw Stock Exchange (WSE) in the years 2010–2019. The study covers both non-financial and financial sector companies. The research focuses on two key phenomena characterising the analysed entities: the composition of statutory bodies in terms of female representation and the financial condition of the companies, assessed through financial data and indicators. The objective of the study is to examine the existence of statistically significant relationships between these two phenomena. Depending on the nature of the companies’ operations, their financial standing is evaluated using different sets of financial indicators.